1992
DOI: 10.1038/356162a0
|View full text |Cite|
|
Sign up to set email alerts
|

Close linkage of glucokinase locus on chromosome 7p to early-onset non-insulin-dependent diabetes mellitus

Abstract: Non-insulin-dependent diabetes mellitus (NIDDM) is a major health problem, affecting 5% of the world population. Genetic factors are important in NIDDM, but the mechanisms leading to glucose intolerance are unknown. Genetic linkage has been investigated in multigeneration families to localize, and ultimately identify, the gene(s) predisposing to NIDDM. Here we report linkage between the glucokinase locus on chromosome 7p and diabetes in 16 French families with maturity-onset diabetes of the young, a form of NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
286
1
7

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(302 citation statements)
references
References 20 publications
5
286
1
7
Order By: Relevance
“…In adulthood these beta cell defects, along with decreased insulin sensitivity would manifest itself in such a way that whole body glucose metabolism was affected. Individuals who have a rare monogenic form of diabetes known as 'maturity onset diabetes of the young' are proof of principle for this theory (7,8). The mutations in these individuals of the glucokinase gene leads to reduced birth weight and development of type 2 diabetes in early adulthood (9) caused by defective glucose sensing in the pancreatic beta cell …”
Section: Epidemiological Findingsmentioning
confidence: 99%
“…In adulthood these beta cell defects, along with decreased insulin sensitivity would manifest itself in such a way that whole body glucose metabolism was affected. Individuals who have a rare monogenic form of diabetes known as 'maturity onset diabetes of the young' are proof of principle for this theory (7,8). The mutations in these individuals of the glucokinase gene leads to reduced birth weight and development of type 2 diabetes in early adulthood (9) caused by defective glucose sensing in the pancreatic beta cell …”
Section: Epidemiological Findingsmentioning
confidence: 99%
“…Given its central role in the regulation of insulin release, it is understandable that mutations in the gene encoding glucokinase (GCK) can cause both hyper-and hypoglycemia. Heterozygous inactivating mutations in GCK cause maturity-onset diabetes of the young (MODY), in which mild hyperglycemia is present at birth but often only detected later in life during screening for other purposes (2,3). Homozygous inactivating GCK mutations result in a more severe phenotype presenting at birth as permanent neonatal diabetes (4).…”
mentioning
confidence: 99%
“…A possible explanation is that the genomic deletion of the 5'-splice site in intron 4 would affect the normal function of the transcriptional machinery, as it has been described by Leroux et al (32). The remaining sequence at the 5'-part ofintron 4 left after the deletion, gggcag (+ 1 to +6), could be recognized as a donor splice site and used with the intron 5 3'-acceptor splice site (ag), instead of the intron 4 (30). The third type of aberrant GCK messenger observed (with an insertion of the first 10 bp from intron 2 between exon 2/exon 3 and the skipping ofexon 5) seems to be rare, since we found it in only one RT-PCR experiment out of five.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic deletion in intron 4 ofthe GCK gene is likely to be responsible for the hyperglycemia in kindred F423 for several reasons: (a) the defect in GCK cosegregated with diabetes in this family, and the likelihood of the odds score (lodscore) for linkage is highly significant (+4.85, i.e., odds for linkage of almost I0':1, data not shown) using an autosomal dominant model (6); (b) this deletion was not present in unrelated normal and late-onset NIDDM individuals; and (c) this deletion resulted in the synthesis of aberrant truncated GCK mRNA species, which probably encode a GCK enzyme with decreased or null activity. A molecular model of the glucokinase protein using the related yeast hexokinase B crystal structure has shown that the region encoded by exon 5, which is missing in splice variant I (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation